Queer Performativity and Sexual Orientation in Christopher Isherwood’s A Single Man - Fadila Ramadhani; Ali Mustofa (LPPM Universitas Bumigora Mataram, 2021)
This research examines the queer performativity and sexual orientation in a novel entitled A Single Man by Christopher Isherwood. The main purpose of this study is to reveal the signs of homosexuality by the protagonist George. The queer studies analytical perspective is used to analyze how the writer constructs the sexual desire of the main character through several events. The study aims to scrutiny the queer performativity and sexual orientation of the main character as a flexible and indeterminate entity exactly in accordance with Butler’s theory, besides, the writer uses Sedgwick’s perspective that explains and describes sexual orientation and gender. The result of the analysis shows some symptoms that exist in George’s character. Living with a different sexual orientation as homosexual is not an easy job when the surrounding is heterosexual society. The situation can create a confusion and over self-identity also an existence of life anxiety. This exhibits negative behavior towards homosexuals and excludes them from autonomous carrying out their identity and essence. This research can give the readers a deeper understanding of what the queer process idea in the field of literature or in the workplace, hence, this also can be a new idea for future readers who are interested in discussing homosexual or gay men’s psychology.